Responsibility of Land Deed Officials (PPAT) for Ethical Violations Acting as IntermediariesLand Sale and Purchase - Fatihah, Istinur; Hafidz, Jawade (TABELLIUS: Journal of Law, 2026)
This study aims to analyze the responsibility of Land Deed Officials (PPAT) for ethical violations acting as intermediaries in land sale and purchase transactions and to examine the legal consequences of sale and purchase deeds made by PPAT acting as intermediaries. This research uses a normative legal research method with a statutory approach and conceptual approach. Legal materials consist of primary legal materials including the 1945 Constitution, Civil Code, Law Number 5 of 1960 concerning Basic Agrarian Regulations, Government Regulation Number 24 of 1997 concerning Land Registration, and Government Regulation Number 24 of 2016 concerning Regulations on the Position of Land Deed Officials, as well as secondary and tertiary legal materials. Data analysis was carried out prescriptively to provide legal arguments regarding the facts or legal events studied. Based on the research, it is concluded that the responsibility of PPAT for ethical violations acting as intermediaries includes administrative responsibility in the form of sanctions from dismissal with dishonor, civil responsibility based on unlawful acts as regulated in Article 1365 of the Civil Code, and criminal responsibility if fulfilling the elements of criminal acts as regulated in Articles 263, 264, or 266 of the Criminal Code. The legal of sale and purchase deeds made by PPAT acting as intermediaries include degradation of evidentiary power from authentic deeds to underhand deeds, potential cancellation of deeds either absolutely or relatively, rejection of registration of transfer of rights at the Land Office, emergence of material and immaterial losses, and legal uncertainties that threaten the integrity of the national land registration system.